The role of interventional radiology for pediatric blunt renal trauma - Lin, Wei-Ching (Ital J Pediatr, 2015)
BACKGROUND: This study aimed to appraise the role of interventional radiology in children with blunt renal trauma. METHODS: The clinical data, injury severity score, days of hospital stay, outcomes and complications of pediatric renal trauma were recorded and evaluated. The two groups: the transcatheter arterial embolization (TAE) group and the non-TAE group were compared for clinical features and laboratory data. RESULTS: Eighteen pediatric patients (12 boys, 6 girls with average age 12.4 ± 4.7 years) with blunt renal injury were included in the study. Six patients underwent angiography because of contrast medium extravasations in the kidney found on computed tomography of which four subsequently underwent a TAE. The clinical features and laboratory data of patients in the TAE and non-TAE groups were not significantly different. All patients were managed successfully by conservative treatment without complications except one in the non-TAE group who required nephrectomy due to renal arterial hypertension directly related to trauma. Both groups had relatively good results and all patients had normal renal function at follow-up. CONCLUSION: TAE is an alternative therapeutic modality for blunt renal injury in children who have contrast medium extravasations in the kidney on angiography.